Improvement of the Specification of the Asphalt Concrete Overlay by Using Polypropylene (Journal of University of Babylon for Engineering Sciences, 2018)
The research aims to prepare high-performance asphalt concrete with good specifications for using in asphalt concrete overlay can resist deformations and problems faced and increase its age service. Used all of polypropylene particles as an additive to  the asphalt concrete type (AC 60-70) by six ratios (1, 2, 3, 4, 5 and 7) % of optimum asphalt content weight,  as an  additive for asphalt mixture with a maximum size of the aggregate (19mm). Study the effect of these additions on the volumetric and the mechanical properties of the asphalt concrete and evaluate its performance through Marshall Method test by take at least three specimens of ratio tested.The results showed that the use of polypropylene particles improve the performance and specifications of asphalt concrete and increase the ability to  resist deformations that are exposed, where  it was concluded that the addition of ratio (4%) of the weight of the asphalt of  polypropylene gives optimum improvement of the performance of the asphalt  concrete overlay, where Marshall stability is increased by 47% and flow decreased by 17% compared to untreated mixtures respectively, with volumetric properties within limitations of the specifications.